PENGARUH PERBANDINGAN SANTAN DAN AIR TERHADAP RENDEMEN, KADAR AIR DAN ASAM LEMAK BEBAS (FFA) VIRGIN COCONUT OIL(VCO) - Moh. Irwanto Ahmd; Lucia C. Mandey; Tineke M. Langi; Jenny E.A. Kandou (Universitas Sam Ratulangi, 2013)
ABSTRACTThis study aims to get a comparison coconut milk and water right on the manufacture Virgin Coconut Oil on yield, moisture content and free fatty acid (FFA), appropriate quality standards and ISO 7381:2008 International Standard(APCC) of Virgin Coconut Oil. This research was conducted in the Laboratory of the Faculty of Agriculture Department of Agriculture fac Sam Ratulangi University. This research used Completely Randomized Design (CRD), which consists of 3 (three) in the treatment of coconut milk and water mixture ratio, with Al treatment 1: 0.5 (1700 ml coconut milk: 850 ml of water); treatment A2 1: 1 (1700 ml 1700 ml coconut water); treatment A3 1: 2 (1700 ml coconut milk: 3400 ml of water), with 3 (three) replications. Observed variables include yield, moisture content, and free fatty acids (FFA). Results in the treatment of Al (1: 0.5) shows the yield value of 15.67 0.13% water content, and free fatty acids (FFA) 0.15%. Results in treatment A2 (I: 1) demonstrate the value of yield 19.72%, water content 0.17%, and free fatty acids (FFA) 0.16%. The yield on the A3 treatment (1: 2) indicates the value of the yield 20%, water content 0.18%, and free fatty acids (FFA) 0.17%. Comparison of the coconut milk and water treatment A3 (1: 2) gave the best results in accordance with ISO 7381:2008 yield value of 20%, water content 0.13% in treatment A1, A2 0.17%, A3 0.18%, while the free fatty acids (FFA) in the treatment of A1 0.15%, 0.16% A2, A3 0, 17%. These results are in accordance with the quality standards according to the Asian Pacific Coconut Community (APCC). Keywords: Virgin Coconut Oil (VCO), coconut milk, Water